Gray Water Conditions on the Growth of Some Natural Ground Cover Plants and the Water Quality of Plants - Sertaç Kaya; Melek Yılmaz Kaya; Ömer Faruk Çoban; Fatma Turan; Nisa Özgen; Engin Eroğlu (Forestist)
Climate change and high water consumption driven by population growth have led to water stress, affecting over 2 billion people worldwide yearly. In the face of scarce water resources, traditional sewage infrastructure, especially during extreme weather, can not handle the water load and leads to pollution in freshwater sources. Treatment of rainwater and graywater can be considered a potential water source to minimize freshwater consumption and enhance water sustainability, offering simple solutions in cities. Recently, the ability of plants to remove toxic metals from dirty waters through their roots have been utilized and then water reused. In this study, a small-scale domestic graywater treatment system was developed under greenhouse conditions as a nature-based solution. In the selection of plants, species naturally distributed in Düzce province, aquatic, riparian, and understory species were preferred. Plants in the system were supplied with graywater and stored. The plants’ purification levels and growth status under polluted water stress were examined. According to the results the amount of anionic substances in stored water, Asplenium scolopendrium L. was observed to have the highest treatment performance among the species. Although Lythrum salicaria L. and Carex pendula Huds. had a lower value compared to other species, they were shown to be a usable species in graywater treatment. Nasturtium officinale R. BR. had a low treatment value and was found to be a pollution-resistant species. As a result, the reuse of water is essential in today’s conditions where climate zones and species distributions are changing. As seen in this study; Although species from natural vegetation have different purification potentials, they offer the opportunity to be used to purify gray water.